Mycobacterium abscessus persistence in the face of Pseudomonas aeruginosa antagonism - Gupta, Rashmi; Schuster, Martin; Rohde, Kyle H. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionChronic bacterial infections are responsible for significant morbidity and mortality in cystic fibrosis (CF) patients. Pseudomonas aeruginosa (Pa), the dominant CF pathogen, and Mycobacterium abscessus (Mab) can individually cause persistent, difficult to treat pulmonary infections. Co-infection by both pathogens leads to severe disease and poor clinical outcomes. Although interactions between Pa and other co-infecting pathogens in CF patients have been the focus of numerous studies, the dynamics of Pa-Mab interactions remain poorly understood.MethodsTo address this knowledge gap, the study examined how Mab and Pa influenced each other through culture-based growth assays and molecular-based dual RNAseq analysis. Growth was measured by CFU determination and luminescence reporter -based readouts.ResultsIn initial studies, we noted that the growth of Pa continued unimpeded in a planktonic co-culture model, whereas Pa appeared to exert a bacteriostatic effect on Mab. Strikingly, exposure of Mab to cell-free spent supernatant of Pa resulted in a dramatic, dose-dependent bactericidal effect. Initial characterization indicated that this potent Pa-derived anti-Mab cidal activity was mediated by a heat-sensitive, protease-insensitive soluble factor of >3kDa size. Further analysis demonstrated that expression of this mycobactericidal factor requires LasR, a central regulator of Pa quorum sensing (QS). In contrast, ΔLasR Pa was still able to exert a bacteriostatic effect on Mab during co-culture, pointing to additional LasR-independent factors able to antagonize Mab growth. However, the ability of Mab to adapt during co-culture to counter the cidal effects of a LasR regulated factor suggested complex interspecies dynamics. Dual RNAseq analysis of Mab-Pa co-cultures revealed significant transcriptional remodeling of Mab, with differential expression of 68% of Mab genes compared to minimal transcriptional changes in Pa. Transcriptome analysis reflected slowed Mab growth and metabolic changes akin to a non-replicating persister phase. A tailored Mab response to Pa was evident by enhanced transcript levels of genes predicted to counteract alkylquinolone QS signals, respiratory toxins, and hydrogen cyanide.DiscussionThe study showed Mab is capable of coexisting with Pa despite Pa’s antagonistic effects, eliciting an adaptive molecular response in Mab. This study provides the first transcriptome-level insight into genetic interactions between the two CF pathogens offering potential strategies for disrupting their communities in a CF lung to improve patient clinical performance. Moreover, identification of a novel antimicrobial natural product with potent cidal activity against Mab could lead to new drug targets and therapies for Mab infections.